Program Penyehatan Masyarakat melalui Posyandu di Desa Kalumpang - Gagah Dwiki Putra Aryono (Pusat Riset dan Inovasi Nasional, 2023)
Integrated service posts (posyandu) are community-sourced health efforts that are managed and organized from, by, for and with the community in implementing health development. Posyandu is an important health service for babies and toddlers. The visit of toddlers at Posyandu is related to the role of the mother as the person most responsible for the health of her toddler, influenced by the mother's visit, namely education, employment status, income level, level of knowledge, age of toddler, and number of children. toddler. Stunting is one of the national development problems in Indonesia which can hamper economic growth, increase poverty and inequality. This research aims to determine the role of posyandu in dealing with stunting in Kalumpang Village, Padarincang District, Serang Regency.